Making Paving Block by Using Plastic Waste Polypropylene (PP) as A Mixture Material of Sand Aggregate (Filter) - Mohamad Mirwan; Firra Rosariawari; Sumaidi (Nusantara Science and Technology Proceedings)
Polypropylane Plastics (PP) is one of the safe plastic materials to use because of the ability to prevent chemical reactions on plastic packaging with food or beverage packaged. The amount of PP plastic waste that is commonly used as a mineral water pack (plastic glass) has the potential to be utilized. Utilization of recycled PP plastic glass waste in this research is used as a mixture material of sand aggregate (filler) of paving-making basic material by testing on paving block sample. In this study determined the ratio of comparisons between raw materials in the form of cement, sand and plastic. The volume of paving material is set at 5 kg, 10% cement percentage by varying sand aggregate 40 - 90% while plastic mixture 0 - 50%, and analyzing compressive strength and water absorption at paving life: 7, 14 and 28 days. To fulfill the need of plastic aggregate in this research, the plastic is chopped up to 1-2 cm size which is meant to blend in making paving block. From the research, it is known that the best compressive strength value of 20% at 7 days to 28 days shows the value of compressive strength up to 13 Mpa and water absorption test reaches 10.17%, it is in accordance with SNI 03-0691 standard -1996 is included in the quality of C and D used for pedestrian and park places.